Protective Role of Cytotoxic T Lymphocytes in Filovirus Hemorrhagic Fever - Warfield, Kelly Lyn (Hindawi Publishing Corporation, 2011)
Infection with many emerging viruses, such as the hemorrhagic fever disease caused by the filoviruses, Marburg (MARV), and Ebola virus (EBOV), leaves the host with a short timeframe in which to mouse a protective immune response. In lethal cases, uncontrolled viral replication and virus-induced immune dysregulation are too severe to overcome, and mortality is generally associated with a lack of notable immune responses. Vaccination studies in animals have demonstrated an association of IgG and neutralizing antibody responses against the protective glycoprotein antigen with survival from lethal challenge. More recently, studies in animal models of filovirus hemorrhagic fever have established that induction of a strong filovirus-specific cytotoxic T lymphocyte (CTL) response can facilitate complete viral clearance. In this review, we describe assays used to discover CTL responses after vaccination or live filovirus infection in both animal models and human clinical trials. Unfortunately, little data regarding CTL responses have been collected from infected human survivors, primarily due to the low frequency of disease and the inability to perform these studies in the field. Advancements in assays and technologies may allow these studies to occur during future outbreaks.